Solve the system of equations by substitution;
![\begin{gathered} y=2x+4---(1) \\ -3x+6y=15---(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qvh98yt8vf7s6bb0hrzwxmx1wfeozg643y.png)
From equation (1), we note that y equals 2x plus 4, hence we substitute this value of y into equation (2)
![\begin{gathered} -3x+6y=15 \\ -3x+6(2x+4)=15 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b999tdv7mqd4n917yy2231zp7ownbjrgq0.png)
Next, we expand the parenthesis on the left side of the equation
![-3x+12x+24=15](https://img.qammunity.org/2023/formulas/mathematics/college/gj1k5bp1k6sk42r52ag4xhv6s7gv6dzyyw.png)
Next we collect all like terms as follows;
![12x-3x=15-24](https://img.qammunity.org/2023/formulas/mathematics/college/fc6u49rtbos2uu7yqgp34ahmh1km45mwp5.png)
Solve this and we arrive at;
![9x=-9](https://img.qammunity.org/2023/formulas/mathematics/college/wxsq5gzf4pfqd4z9q4qv3ld88s3oxl28v4.png)
Divide both sides by 9
![\begin{gathered} (9x)/(9)=-(-9)/(9) \\ x=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2c4gi129ki09ygydygqq76b8kq6j6su4jn.png)
We can now substitute for x = -1 into equation (1)
![\begin{gathered} y=2x+4 \\ y=2(-1)+4 \\ y=-2+4 \\ y=4-2 \\ y=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/98r3im969iyyo4d3zp1u137g9tez7x9ue5.png)
The solution is
x = -1, y= 2